EVALUATION OF BONE HEALING TIME AFTER INTERNAL FIXATION SURGERY IN PATIENTS WITH OSTEOPOROTIC FRACTURES - Thành Toàn, Võ; Phan Vĩnh Toàn, Đặng; Trọng Sỹ, Nguyễn (Journal of Health and Aging, 2025)
To evaluate the impact of osteoporosis on bone union time. The study involved 405 fracture patients divided into two groups: Group A, consisting of 242 patients with fractures and osteoporosis; and Group B, consisting of 163 patients with corresponding fractures but without osteoporosis, from January 2020 to January 2024. The osteoporotic patient group was older, with a majority being female (p < 0.05). The most common fracture type was intertrochanteric, with 81 cases accounting for 20% of all fractures. Of these, the majority were in patients with osteoporosis (52 patients, 64.2%). Osteoporosis prolonged the bone union time in patients with intertrochanteric fractures and femoral shaft fractures. Bone healing time is affected by osteoporosis at intertrochanteric and femoral shaft fracture.